The British Imperial Army in the Middle East morale and military identity in the Sinai and Palestine campaigns, 1916-18 - Kitchen, James E. (War, culture and society, 2014)
The First World War has often been understood in terms of the combat experiences of soldiers on the Western Front; those combatants who served in the other theatres of the war have been neglected. The British Imperial Army in the Middle East explores the combat experiences of these soldiers. By taking a transnational and imperial perspective on the First World War, this book ensures that the campaigns in Egypt and Palestine are considered in the wider context of an empire mobilised to fight a total and global war.